THE INFLUENCE OF DOMESTIC INVESTMENT, FOREIGN DIRECT INVESTMENT AND THE ABSORPTION OF LABOR TOWARD THE GROWTH OF LOCAL ECONOMIC GROWTH AND THE AMOUNT OF PEOPLE WHO LIVE IN POVERTY IN REGENCY/CITY IN WEST KALIMANTAN - B61109035, TETTY AGUSTINI (Jurnal Ekonomi Daerah (JEDA), 2016)
The development in the regency/ city in West Kalimantan is aimed at establishing local economic growth and society welfare. In order to accelerate local development, there are some factors needed to influence local economic growth such as investment and labor. The purposes of the research are to know: 1) The influence of Domestic Investment toward the growth of local economic growth in regency/ city in West Kalimantan. 2) The influence of Foreign Investment toward the growth of local economic growth in regency/ city in West Kalimantan. 3) The influence of the absorption of labor toward the growth of local economic growth in regency/ city in West Kalimantan. 4) The influence of Economic Growth toward the amount of people who live in poverty in regency/ city in West Kalimantan. The results of the research show that: 1) Domestic Investment influnces positively and significant toward growth of local economic growth in regency/ city in West Kalimantan. 2) Foreign Investment influences positively and significant toward growth of local economic growth in regency/ city in West Kalimantan. 3) The Absorption of labor influences positively and is significant toward the amount of local economic growth in regency/ city in West Kalimantan. 4) Economic Growh influences negatively and significant toward the amount of people who live in poverty in regency/ city in West Kalimantan. Keywords : Domestic Investment, Foreign Investment, Labor Absorption, Economic Growth, The Amount of People Who Live in Poverty